Association of CALLY index and CLR with COPD risk in middle-aged and older Americans: evidence from NHANES 2017–2020 - Jiaji Zhou; Jiaji Zhou; Wenyi Du; Hanzhou Huang; Hanzhou Huang; Yongqi Chen; Yongqi Chen; Leyan Chen; Leyan Chen; Mingfeng Zheng; Mingfeng Zheng (Frontiers in Medicine)
BackgroundChronic obstructive pulmonary disease (COPD) is marked by restrictions on airflow, leading to a gradual and irreversible reduction in lung function. This study assessed the predictive value of hematological inflammatory biomarkers, specifically the C-reactive protein-albumin-lymphocyte (CALLY) index and the C-reactive protein to lymphocyte ratio (CLR), for determining COPD risk in United States adults aged 40 and above.MethodsData were sourced from the National Health and Nutrition Examination Survey (NHANES) covering the period from 2017 to March 2020. The relationship between inflammatory markers, including the CALLY index, CLR, and their components, and COPD was assessed using multivariate logistic regression. Subgroup analyses explored the relationship between the CALLY index, CLR, and COPD, while restricted cubic spline (RCS) analyses evaluated potential non-linearity. The predictive performance of these biomarkers for COPD risk was assessed using receiver operating characteristic (ROC) curve analysis.ResultsAfter controlling for confounders, for every one-unit increase in the CALLY index (converted to natural logarithm), the prevalence of COPD decreased by 19% (OR = 0.81, 95% CI: 0.71–0.92, P = 0.001). Conversely, for every one-unit increase in the CLR (converted to natural logarithm), the prevalence of COPD increased by 23% (OR = 1.23, 95% CI: 1.08–1.40, P < 0.001). The linear negative correlation between the CALLY index and COPD was demonstrated by using RCS curves, while the CLR exhibited a positive association. After being fully adjusted, both the CALLY index and the CLR yielded an adjusted area under the curve (AUC) of 0.831 for predicting the risk of COPD, demonstrating excellent predictive capability.ConclusionThe study identifies a linear negative relationship between the CALLY index and COPD, unaffected by potential confounders. A higher CLR is linked to an elevated risk of COPD development. Both the CALLY index and CLR were superior in predicting the risk of developing COPD. Our findings emphasize that the CALLY index and CLR may be a new inflammatory early warning biomarker for COPD.